2019
DOI: 10.3390/rs11080991
|View full text |Cite
|
Sign up to set email alerts
|

Increasing Precision for French Forest Inventory Estimates using the k-NN Technique with Optical and Photogrammetric Data and Model-Assisted Estimators

Abstract: Multisource forest inventory methods were developed to improve the precision of national forest inventory estimates. These methods rely on the combination of inventory data and auxiliary information correlated with forest attributes of interest. As these methods have been predominantly tested over coniferous forests, the present study used this approach for heterogeneous and complex deciduous forests in the center of France. The auxiliary data considered included a forest type map, Landsat 8 spectral bands and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
4
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2
1

Relationship

1
9

Authors

Journals

citations
Cited by 12 publications
(6 citation statements)
references
References 84 publications
0
4
0
Order By: Relevance
“…A common theme in these studies is the direct examination of synthetic model prediction errors (e.g., using cross validation) without formulating the models in a design-based or composite modeling framework to mitigate potential synthetic estimator bias (cf. McRoberts et al, 2013;Irulappa-Pillai-Vijayakumar et al, 2019;McConville et al, 2020). In model-assisted applications the usual goal is to increase the precision of population-level estimates, and less often to produce estimates for domains that divide a larger population into small areas where direct estimator instability can be a concern.…”
Section: Model-assisted Estimationmentioning
confidence: 99%
“…A common theme in these studies is the direct examination of synthetic model prediction errors (e.g., using cross validation) without formulating the models in a design-based or composite modeling framework to mitigate potential synthetic estimator bias (cf. McRoberts et al, 2013;Irulappa-Pillai-Vijayakumar et al, 2019;McConville et al, 2020). In model-assisted applications the usual goal is to increase the precision of population-level estimates, and less often to produce estimates for domains that divide a larger population into small areas where direct estimator instability can be a concern.…”
Section: Model-assisted Estimationmentioning
confidence: 99%
“…The NFI data came from 755 plots measured from 2010 to 2014. Irulappa-Pillai-Vijayakumar et al (2019) goes into considerable detail about the significant effort invested and difficulties encountered in: (1) transforming digital aerial photography and ALS into 3D digital terrain models that could be used to estimate canopy height models for two different time periods (2008 and 2014); and (2) using the estimated changes in height between 2008 and 2014 to estimate changes in other forest attributes, such as stand density, basal area and several different types of volume. Finally, auxiliary data for all 11 variables were converted to a spatial resolution of 30 m to conform with the spatial resolution of the TM sensor aboard LANDSAT.…”
Section: Rationale For Sae Researchmentioning
confidence: 99%
“…Their SE estimates varied from 2% to 4%, although SE estimates were not reported for specific forest species. Irulappa-Pillai-Vijayakumar et al [65] reported V estimates for a French region using NFI field plot data and remotely sensed data. They reported SE estimates of approximately 3% for oak V estimates and 5.76% for PS.…”
Section: Effects Of Sampling Variability For the Model Calibration Datasmentioning
confidence: 99%